Anti-Oxidant, Anti-Inflammatory and Antiproliferative Effect of Tecoma Stans Fruit - Kashyap, Arun Kumar; Loha, Anita; Kashif, Mohammad (International Journal of Computer Sciences and Engineering, 2025)
Tecoma stans, member of family Bignoniaceae, is a popular ornamental plant grown for its bright yellow flowers. It is widely used for its medicinal properties in curing diabetes, digestive problems and yeast infections. Almost all parts (leaves, root, flower, seed, fruit, and bark) of the plant is have its medicinal use. In present study fruit extract was prepared and checked for its antioxidant, free radical scavenging ability and antiproliferative activities in cancerous cell line. Ethyl acetate and methanol extracts exhibited high antioxidant activity and free radical scavenging capacity. The expression of the proinflammatory gene(s) cox-2, IL1β, TNFα were checked in a cancerous cell line treated with the methanol extract in comparison to the untreated cells. The expression of all three genes was significantly reduced in the treated cancerous cells in comparison to untreated ones. Further when the cancerous cell line was treated with methanol extract it exhibited potent anti-proliferative activity and significantly changed the morphology of the cancerous cell